Priorities for women with lymphoedema after treatment for breast cancer: population based cohort study. (21st June 2011) - Girgis, Afaf; Stacey, Fiona; Lee, Teresa; Black, Deborah; Kilbreath, Sharon
Abstract : Objective To explore the perceived unmet needs among women treated for breast cancer and in whom symptoms and signs indicate the presence of lymphoedema. Design Population based cross sectional survey with a purpose designed questionnaire (60 items). Setting Cancer registries of New South Wales, Victoria, and South Australia. Participants 237 women with symptoms and signs indicative of lymphoedema from an initial 1930 eligible women. Main outcome measure Unmet needs in the previous month across psychological, health system and information, physical and daily living, patient care and support, sexuality needs, body image, and financial domains. Results The 10 items most commonly identified as a "moderate to high current need" included having their doctor and allied health workers being fully informed about lymphoedema, acknowledge the seriousness of the condition, and be willing to treat it. Women also wanted access to up to date treatments, both mainstream and alternative, and financial assistance for their garments. The three factors that explained most of the variance were: information and support (11 items), which accounted for 49% of the variance; body image and self esteem (seven items; 7% variance); and health system (seven items; 5% variance). Examination of these three factors showed that while the levels of need were generally low, they were common. Conclusion To address the needs of women with lymphoedema and perhaps to prevent progression of lymphoedema, it is important that practitioners do not dismiss mild symptoms and that women are referred to an appropriate specialist.